Policy Implementation in the Development of Mangrove Bulaksetra Educational Tourism Objects in Babakan Village, Pangandaran District, Pangandaran Regency - Adi Cakranegara, Pandu (Decision, 2022)
This research has a problem background to analyze policy implementation in the development of the Bulaksetra mangrove educational tourist attraction in Babakan Village, Pangandaran District, Pangandaran Regency. Descriptive research uses a qualitative approach. The theory used in this research uses theories and indicators from George C. Edward III. The techniques used by researchers in this research are observation, interviews and documentation. Informants were determined using purposive sampling techniques. The results of this research are (1) communication, where the village government is quite good at communicating but not yet optimal in communication consistency so that the community does not understand the content of the policy, (2) resources, the village government and the PPKP group already have competent staff but lack coordination and Facilities that are not met make the implementation of policy programs limited, (3) disposition (attitude), the village government has an enthusiastic attitude towards the program, but has not yet optimally coordinated between fellow policy implementers, (4) the organizational structure has SOPs as the main reference in implementing policy program but the stages of authority and responsibility of each unit are not yet optimal. The conclusion of this research is that there are supporters and obstacles in implementing policies in developing Bulaksetra mangrove educational tourism objects which are found in the dimensions of communication, resources, disposition and organizational structure.